Effectiveness of Behavioral Counseling Theory with Lesson Study Through Modeling Techniques to Improve The Nature of Sympathy and Empathy Class Second Grade MIA 8 SMA Negeri 1 Denpasar - I Gusti Ngurah Adi Mahendra; I Ketut Dharsana; Ni Ketut Suarni (RedwhitePress)
This research is a quasi research (